Do exporters import gender inequality? - Olga Lark; Josefin Videnord (Lund University, School of Economics and Management, Department of Economics, 2023)
We examine whether exposure to gender inequality at export destinations affects the gender wage gap in exporting firms. We motivate the analysis through a stylized model where wages depend on worker productivity, and men have a comparative advantage when trading with gender-unequal countries due to customer discrimination. Empirically, we use high-quality matched employer- employee data from Sweden and calculate how exposed firms are to country-level gender inequality through their export destinations. Although increased export intensity on average leads to a wider within-firm gender wage gap, the effect is entirely driven by trade with gender-unequal countries; we find no impact on the gender wage gap when firms increase their exports to countries with gender-equality levels close to that of Sweden. Female managers, who are most likely to interact with foreign customers, experience the most pronounced negative relative wage effects.
Keywords: J16; J31; F14; F16; F66; 330; Export; International trade; Gender wage gap; Gender inequality; Customer discrimination; Gender inequality index